Ambient Networks 16th IFIP/IEEE International Workshop on Distributed Systems: Operations and Management, DSOM 2005, Barcelona, Spain, October 24-26, 2005, Proceedings - Jürgen, Schönwälder; Serrat, Joan (Computer Communication Networks and Telecommunications, 2005)
This volume of the Lecture Notes in Computer Science series contains all the papersacceptedforpresentationatthe16thIFIP/IEEEInternationalWorkshop on Distributed Systems: Operations and Management (DSOM 2005), which was held at the University Polit` ecnica de Catalunya, Barcelona during October 24- 26, 2005. DSOM 2005 was the sixteenth workshop in a series of annual workshop and it followed the footsteps of highly successful previous meetings, the most - cent of which were held in Davis, USA (DSOM 2004), Heidelberg, Germany (DSOM 2003), Montreal, Canada (DSOM 2002), Nancy, France (DSOM 2001), and Austin, USA (DSOM 2000). The goal of the DSOM workshop is to bring togetherresearchersintheareasofnetworks,systems,andservicesmanagement, from both industry and academia, to discuss recent advances and foster future growth in this ?eld. In contrast to the larger management symposia, such as IM (Integrated Management) and NOMS (Network Operations and Management Symposium), the DSOM workshops are organized as single-track programs in order to stimulate interaction among participants.